The characteristic differences in exhaust emissions, and fuel consumption analysis of unleaded gasolines produced by different oil companies in the Turkish market - Ergenç, A; Yavasliol, I; Ayhaner, M; Dicle, H (INDERSCIENCE ENTERPRISES LTD, 2005)
In Turkey, the differences in the properties of gasolines that are taken from different petrol stations are intensively discussed. By taking this as a starting point, the main target of this project is to examine these differences and how they affect exhaust emissions. The properties of nine gasoline samples taken from nine different petrol stations that belong to three different oil companies were studied. The values obtained are compared with European and Turkish National norms, and the differences in the values are described. The exhaust emissions test equipment and test methods and outputs are explained. The results show that the fuels that have high sulfur, low volatility and low Reid vapour pressure exhibit increased emission values.
Keywords: exhaust emissions; gasoline; Turkey; vehicle exhausts; Environmental Sciences & Ecology